Therapeutic Communication With Patients Who Are Victims Of Violence - Nur, Kholid Rosyidi Muhammad; Kurniyawan, Enggal Hadi; Kurniawan, Dicky Endrian; Afandi, Alfid Tri (Rajaki of Tulip Medika Publisher, 2024)
Victims of violence often experience trauma that can have a prolonged effect as a result of the violence, so it is necessary to make an effort to overcome these problems. For this reason, a nurse needs to carry out effective therapeutic communication to overcome these problems. Violence can be carried out by someone verbally, directed at themselves, other people, and even the environment. At this time, violence has become commonplace in the public's ears. This affects the soul, namely the psychology of a victim who experiences this violence. Therapeutic communication from a nurse is essential because it can control a person's mental state so that a nurse can become a place of conversation for victims of violence. This research aims to determine the relationship between therapeutic communication for victims of violence so that nurses can control the patient's mental health. The literature review used in making this article was done through several databases, including Google Scholar, ScienceDirect, and Garuda. The review literature used is vulnerable to publication in 2018-2023. The result of these articles is that through therapeutic communication, psychologists were able to create a sense of security and trust, which facilitated the recovery process for the victims. Therapeutic communication has a vital role in helping adolescents who experience sexual violence overcome the traumatic impact. Therapeutic communication also can help to reduce signs and symptoms of violent behavior. Therapeutic communication can increase the victim's self-esteem and dignity so they can live a more vibrant life with more enthusiasm. Therapeutic communication also plays a vital role in the mental recovery process that occurs in victims of violence. With the implementation of therapeutic communication, we hope that patients or victims of violence will be able to fight their trauma and various mental disorders that they are currently suffering from. In this case, nurses have a role in implementing their ability to therapeutic communication to overcome mental disorders and trauma in patients with victims of violence.